Comparative Analysis of Strength and Deformation Behavior of Cemented Tailings Backfill under Curing Temperature Effect - Zheng Pan; Keping Zhou; Yunmin Wang; Yun Lin; Fahad Saleem (Materials, 2022)
Mineral resources are increasingly being developed in cold and permafrost regions. However, the mechanical and physical properties of cemented tailings backfill (CTB) cured at normal temperature are no longer applicable. To clarify the reasons for this variability, a series of tests were performed. The mechanical properties of CTB with different cement–tailings ratios (CTR, 1:4, 1:8, 1:12, 1:16, and 1:20) were tested at different curing ages (3, 7 and 28 days) and curing temperatures (20 °C, 5 °C, −5 °C, and −20 °C). The differences of CTB in mechanical and physical properties under positive- and negative-temperature curing conditions were analyzed, and the microscopic failure process of CTB under negative-temperature curing conditions was discussed. The results revealed that the mechanical properties and deformation behavior of CTB under positive- and negative-temperature curing conditions were different. The frozen CTB had higher early strength than the standard-temperature curing condition (20 °C), and the lower the temperature, the higher the early strength. The low-temperature curing condition, on the other hand, was not beneficial to CTB’s long-term strength. The low-temperature curing condition was not conducive to the long-term strength of CTB. After yielding, strain hardening and strain softening appeared in the deformation behavior of frozen backfill, indicating ductility. In contrast to the typical-temperature curing condition, the frozen CTB showed a new failure pattern that has little relation to curing time or CTR. Furthermore, the failure process of frozen backfill was reviewed and studied, which was separated into four stages, and altered as the curing time increased. The results of this study can act as a guide for filling mines in permafrost and cold climates.